2016
DOI: 10.1073/pnas.1523412113
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of interdependent directed networks

Abstract: Increasing evidence shows that real-world systems interact with one another via dependency connectivities. Failing connectivities are the mechanism behind the breakdown of interacting complex systems, e.g., blackouts caused by the interdependence of power grids and communication networks. Previous research analyzing the robustness of interdependent networks has been limited to undirected networks. However, most real-world networks are directed, their in-degrees and out-degrees may be correlated, and they are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
98
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(105 citation statements)
references
References 41 publications
3
98
1
Order By: Relevance
“…These kinds of interdependent networks were firstly constructed and the percolation process of such systems studied by Parshani in Reference [2]. In addition, there are few bidirectional (or undirected) dependency links similar to those shown as Figure 1a, and most of the dependency links in interdependent networks are directed [23]. For example, a node in the control network may control a power network node, but this power node is not necessarily responsible for the power supply of this control node, i.e., the power node depends on the control node but not vice versa, which constitutes unidirectional dependency.…”
Section: Interdependent Network With No-feedback Dependencymentioning
confidence: 99%
See 1 more Smart Citation
“…These kinds of interdependent networks were firstly constructed and the percolation process of such systems studied by Parshani in Reference [2]. In addition, there are few bidirectional (or undirected) dependency links similar to those shown as Figure 1a, and most of the dependency links in interdependent networks are directed [23]. For example, a node in the control network may control a power network node, but this power node is not necessarily responsible for the power supply of this control node, i.e., the power node depends on the control node but not vice versa, which constitutes unidirectional dependency.…”
Section: Interdependent Network With No-feedback Dependencymentioning
confidence: 99%
“…Coupling preference determines the way that dependency links are established between subnetworks, such as assortative coupling, disassortative coupling, and random coupling based on node degree or betweenness [21]. The dependency link can be either directed [22,23] or undirected [13,14]. Fu et al [24] investigated the influence of the dependency link direction on the robustness of interdependent networks, and found that the robustness of directed interdependent networks was worse than undirected ones.…”
Section: Introductionmentioning
confidence: 99%
“…In network science, systems composed of multiple interacting networks [24][25][26][27][28] have attracted considerable attention owing to the discovery of novel structural and dynamical features that differ from those observed in isolated networks. In the past decade, the mathematical frameworks for characterizing the robustness of a network of networks [27] or multilayer networks [28] have been studied in various settings, such as full interdependency [24], partial interdependency [29], interconnections [30], spatially embedded networks [31], multiple supports [32], directed networks [25], targeted attacks [33], multiple networks [34], and many more. The robustness of multilayer networks has a broad impact on infrastructure networks [35], ecological systems [36], social networks [37], and financial networks [38].…”
Section: Introductionmentioning
confidence: 99%
“…None of the previously described frameworks can be directly applied to multilayer biological molecular networks. Those approaches are, for the most part, agnostic of their applied setting and deal with networks of the same type, which are either all undirected [27] or all directed [25,50], and in which where the interdependence relations are random. By contrast, biological networks include both directed and undirected network layers, and the non-randomly connected links between layers are of different types.…”
Section: Introductionmentioning
confidence: 99%
“…Because these complex networks play an important role in society, their robustness is pivotal234. However, most of these infrastructures have been found to be heterogeneous and to have a power-law degree distribution156.…”
mentioning
confidence: 99%